TINGKAT KEMAMPUAN TENDANGAN SABIT PADA PERGURUAN PENCAK SILAT SETIA HATI TERATE (PSHT) RAYON BALONGASEM KECAMATAN LENGKONG KABUPATEN NGANJUK - Kustoro, Arif; Sinto Raya, Garnika Ade (Dharmas Journal of Sport, 2024)
The sickle kick is one of the most important kick techniques in pencak silat. This study aims to examine the level of sickle kick ability among members of the Setia Hati Terate Pencak Silat College (PSHT) Balongasem Rayon, Lengkong District, Nganjuk Regency. One of the kicking techniques that is often used in attacks is the sickle kick. In this case, a survey conducted on the ability of sickle kicks in the training of Balongasem Rayon athletes, Lengkong District, Nganjuk Regency was attended by 18 participants. The type of research used isiquantitative with survey methods. Instrumentitest using testi speedi kick isickle Results Research shows that in the "very good" category there were 3 participants (16.67%), in the fair category there were 12 participants (66.67%), and in the very poor category there were 3 participants (16.67%). It is hoped that this research will provide an overview of the mastery of the sickle kick technique and the factors that influence it, such as the training curriculum, quality of trainers, and member motivation. The results of the research can be used as material for evaluation and improvement in the training program at PSHT Rayon Balongasem in order to improve the sickle kicking abilities and achievements of its members in various pencak silat competitions.